Adaptation of parasitological identification techniques for quantification of gastrointestinal parasites in primates (Research, Society and Development, 2021)
Gastrointestinal parasites studies in captive primates are important tools for monkey population management because contributes to the assessment of your health, besides allowing the evaluation of the efficiency of the management routines. Techniques that can identify and quantify parasites can help in parasitological evaluation. Therefore, the present work aimed to evaluate techniques for identification and quantification of gastrointestinal endoparasites in primates, measure the degree of parasitic infection in the samples and suggest methodological adaptations in the identification techniques, enabling its use also in the quantification of eggs per gram. Using fecal samples of 39 primates allocated in Wild Animals Screening Center in the city of Vitoria da Conquista, three identification techniques were evaluated - direct exam, spontaneous sedimentation and Willis technique, using the McMaster quantification technique as the gold standard. Three parasites - Ancylostoma sp., Enterobius sp. and Strongyloides sp. - were identified. The most efficient identification technique was direct exam, followed by spontaneous sedimentation and Willis technique. Adaptations were made on the utilized identification techniques - direct exam and spontaneous sedimentation - aiming to a better evaluation of the degree of infection presented by these primates. McMaster's technique has limitations in the quantification of parasites in milder infections, while it was possible to quantify them using the adapted Direct and Sedimentation techniques, indicating the possibility of using these identification techniques (qualitative) for the quantification of parasites in feces of non-human primates.